2011
DOI: 10.1016/j.jiph.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

An educational program about premarital screening for unmarried female students in King Abdul-Aziz University, Jeddah

Abstract: The educational program was successful in improving students' knowledge about the PMS. Conduction of similar educational programs and adding PMS in the curriculum of secondary and university education are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
64
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 17 publications
12
64
2
5
Order By: Relevance
“…This result agrees with Abd El-Ghany et al (2010), who mentioned that few numbers of non-medical and medical groups had a good level of knowledge score about premarital counseling. It is also in line with the study done by Ibrahim et al (2011), who reported that students' knowledge about PMS program was low in the pre-test (16,26) . As regards to the student's attitude toward premarital screening and counseling, the results of the present study showed significant improvement in most items of attitudinal scale among studied groups of students was detected during the post test.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This result agrees with Abd El-Ghany et al (2010), who mentioned that few numbers of non-medical and medical groups had a good level of knowledge score about premarital counseling. It is also in line with the study done by Ibrahim et al (2011), who reported that students' knowledge about PMS program was low in the pre-test (16,26) . As regards to the student's attitude toward premarital screening and counseling, the results of the present study showed significant improvement in most items of attitudinal scale among studied groups of students was detected during the post test.…”
Section: Discussionsupporting
confidence: 90%
“…Premarital screening and counseling is one of the important strategies for prevention of genetic disorders, congenital anomalies, and common medical psychosocial marital problems (16) . The aim of the current study was to assess knowledge and attitude toward pre-marital screening and counseling among medical and non-medical female students at El Minia University and evaluating the effectiveness of educational program on improving the students' knowledge and attitude toward pre-marital screening and counseling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study done in India shows that 53.27% participants stated, thalassemia is a result of consanguineous marriages, while in a study done in Denizli shows decreased results where more than half of the population knew that consanguineous marriages increases genetic disease but nearly half of the population knew that risk of having thalassemia could be increased by consanguinity, these results are much on lower side than previously done studies in saudia where 84%, 89.6% of participants agreed that consanguinity increases the risk for genetic diseases like thalassemia 19,31 .…”
Section: Fig 2: Awareness About Thalassemia Prevention (N=130) 4 Discmentioning
confidence: 84%
“…Another study shows that the main sources of information on genetic diseases were friends and family 19 . Another study reported that nearly one third of the participants' source of information on PMS was media 20 .…”
Section: Fig 2: Awareness About Thalassemia Prevention (N=130) 4 Discmentioning
confidence: 99%